France’s Ottoman policy from the siege of Vienna to the Treaty of Karlowitz (1683–1699) - Bérenger, Jean (Balcanica Posnaniensia. Acta et studia, 2003)
France’s policy toward the Ottoman Empire revealed deep ambivalence. While refusing to join the Holy League initiated by Pope Innocent XI, Louis XIV chose to maintain a posture of benevolent neutrality toward the Ottoman Empire, guided by strategic, economic, and religious interests. The aim of the article is to examine the logic behind this seemingly contradictory French policy: on the one hand, preserving commercial interests in the Levant and protecting Christian communities under Ottoman rule, on the other, weakening the House of Austria by sustaining a counter-alliance with the Sublime Porte. The article also explores how this policy influenced Franco-Ottoman diplomatic relations in the lead-up to and during the Karlowitz negotiations. The analysis is based on a wide array of French diplomatic sources (correspondence, instructions, memoranda), Franco-Ottoman capitulations, and French and European secondary literature. France, without directly engaging in the war, was able to exert significant influence over the Ottoman Empire. Close cooperation between France and the Porte – especially between 1689 and 1695 – included diplomatic, economic, and sometimes logistical support. However, beginning in 1696, France gradually distanced itself from the alliance, culminating in the Treaty of Ryswick (1697) and its implicit abandonment of the Ottomans. The Treaty of Karlowitz symbolized the weakening of French influence in the eastern Mediterranean. The article highlights a realpolitik approach, driven more by the interests of the French monarchy than by religious or ideological solidarity.